The Criminogenic and Noncriminogenic Treatment Needs of Intimate Partner Violence Offenders - Hilton, N. Zoe (International journal of offender therapy and comparative criminology, 2018)
The criminogenic needs of general offenders have been empirically studied, but the criminogenic treatment needs of intimate partner violence (IPV) offenders, or how they compare with other violent or nonviolent offenders, have not been as thoroughly explored. Therefore, we examined and compared the criminogenic and noncriminogenic needs of 99 IPV offenders, 233 non-IPV violent offenders, and 103 nonviolent offenders, all of whom were men who had undergone institutional forensic assessment. Results indicated that IPV offenders had more treatment needs than the other two offender groups, including the Central Eight criminogenic needs. These findings support a focus on criminogenic treatment needs in batterer intervention programs for men, consistent with the principles of effective intervention for offenders.